2009
DOI: 10.1073/pnas.0812671106
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regulation of mitochondrial function by glucocorticoids

Abstract: Glucocorticoids play an important biphasic role in modulating neural plasticity; low doses enhance neural plasticity and spatial memory behavior, whereas chronic, higher doses produce inhibition. We found that 3 independent measures of mitochondrial functionmitochondrial oxidation, membrane potential, and mitochondrial calcium holding capacity-were regulated by long-term corticosterone (CORT) treatment in an inverted ''U''-shape. This regulation of mitochondrial function by CORT correlated with neuroprotection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
329
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 415 publications
(354 citation statements)
references
References 29 publications
19
329
3
3
Order By: Relevance
“…Significant difference between stress control and stress treated with honey ( ♣ P < .05). both glucocorticoid exposure and oxidative stress may induce neuronal oxidative stress through enhanced mitochondrial respiration and oxidative phosphorylation [50], and promote gliogenesis over neurogenesis in hippocampal neural stem cell progenitors [51,52]. Correspondingly, we demonstrated that the stressed rats possessed a lower number of pyramidal neurons in the hippocampus as well as in the mPFC compared to the nonstressed rats.…”
Section: Discussionmentioning
confidence: 52%
“…Significant difference between stress control and stress treated with honey ( ♣ P < .05). both glucocorticoid exposure and oxidative stress may induce neuronal oxidative stress through enhanced mitochondrial respiration and oxidative phosphorylation [50], and promote gliogenesis over neurogenesis in hippocampal neural stem cell progenitors [51,52]. Correspondingly, we demonstrated that the stressed rats possessed a lower number of pyramidal neurons in the hippocampus as well as in the mPFC compared to the nonstressed rats.…”
Section: Discussionmentioning
confidence: 52%
“…In both cultured neurons and in prefrontal cortex tissue, GC treatment showed a biphasic effect on mitochondrial oxidation, membrane potential, and calcium capacity, with lower doses improving these measures and higher or chronic doses and treatments causing deficits. These effects were correlated with the neuroprotective effects of the GC corticosterone (15). Previous studies have established that GRs can alter the transcription of mitochondrial genes in cultured cells, but GR regulation of mtDNA transcription has not yet been confirmed as occurring in vivo (13).…”
mentioning
confidence: 62%
“…Steroid hormone receptors, including estrogen receptors and GRs, translocate into brain mitochondria. Studies in cultured cells suggest that mtDNA contains GC response elements (GREs) and that these may have a functional role in regulating mtDNA transcription (13)(14)(15)(16)(17)(18). In both cultured neurons and in prefrontal cortex tissue, GC treatment showed a biphasic effect on mitochondrial oxidation, membrane potential, and calcium capacity, with lower doses improving these measures and higher or chronic doses and treatments causing deficits.…”
mentioning
confidence: 99%
“…Immunoprecipitation was performed as previously described with minor modifications (37). Detailed methods are provided in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%